Academic Achievement and Conceptual Understanding of Electrodynamics: Applications Geoelectric Using Cooperative Learning Model - Prastowo, Rizqi; Huda, Syamsul; Umam, Rofiqul; Jermsittiparsert, Kittisak; Prasetiyo, Andika Eko; Tortop, Hasan Said; Syazali, Muhamad (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
Students' comprehension of the theory is often implemented as an effort to improve their achievements. However, other learning processes are rarely carried out by teachers, such as the practice or tools uses as the lesson application. The purpose of this study is to analyze the learning effectiveness by applying the geophysical surveys practice method or the use of environmental geophysics tools. The assessment of students' abilities is based on the interpretation results of environmental geophysical survey data and the presentations and discussions about the results of interpretation. The TGT Cooperative learning model was used with a quasi-experimental method and quantitative design. Data collection was carried out using a series of research instruments in the form of questionnaires. The results of the study were based on comparisons between the experimental class and the control class. The results show that the experimental class has excellent findings. 1) Based on the results of the post-test, the TGT cooperative learning method is very effective in this study, because teamwork can maintain students' enthusiasm and understanding during the learning process. 2) Retrieval of field data makes students better understand the application of geoelectric concepts and determination of rock resistivity.